Answer:
x = 6
Explanation:
We want to solve:
![(-2)/(3) x+9=(4)/(3) x-3](https://img.qammunity.org/2021/formulas/mathematics/college/4de6eew1hcamwwkjz418g3deys3v3v3xwc.png)
First, isolate the variable by moving all the terms with x to one side and all the constants to the other side:
![(4)/(3)x +(2)/(3) x=9+3](https://img.qammunity.org/2021/formulas/mathematics/college/4jz9ouw7x196pvjju7gtmy5dcauvxx4rb7.png)
Combining the fraction on the left, we get:
![(6)/(3) x=12](https://img.qammunity.org/2021/formulas/mathematics/college/oe11v1zk1judy4wlkinwdzo68d6zd6dhk7.png)
6/3 = 2, so:
2x = 12
Dividing both sides by 2 yields:
x = 6